Independent State of Samoa Early Childhood Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies which affect young children in the Samoa. This report is part of a series of reports prepared by the World Bank using the SABER-ECD framework. The country report includes analysis of early learning, health, nutrition, social and child protection policies and interventions in Samoa, along with regional and international comparisons. The SABER-ECD initiative is designed to enable ECD policy makers and development partners to identify opportunities for further development of effective ECD systems. The SABER-ECD classification system does not rank countries according to any overall scoring; rather, it is intended to share information on how different ECD systems address the same policy challenges. This country report presents a framework to benchmark the Samoa s ECD system; each of the nine policy levers are examined in detail and some policy options are recommended.